Plagiarism from the Perspective of Distance Higher Education Students - Campanhão, Ligia Maria Barrios; Medeiros, Bruno Cesar Cassani; Dos Santos, Stefanny Batista; Tito, Ana Yenny Molleapaza; Curcio, Ana Paula; Belo, Juliana Morais; Pereira, Luís Eduardo Santos [UNESP]; Haas, Celia Maria (FapUNIFESP (SciELO), 2024)
This study aimed to investigate the knowledge of plagiarism among undergraduate students at a distance education univer-sity. A questionnaire was applied to the students, and the content of two courses and institutional documents were analyzed to identify guidelines regarding plagiarism. Plagiarism was not discussed in the courses, and institutional documents provided inconsistent guidance on how to address it. Although students claim to know what plagiarism is, the ma-jority associate it solely with copying content without pr oper referenc-ing or citation. According to the students, the main reasons leading to plagiarism are a lack of organization and motivation for studying, and a lack of skills for academic writing.
O Plágio a partir da Percepção dos Alunos da Educação Superior a Distância
Keywords: Distance Education; Higher Education; Plagiarism; Scientific Writing; Undergraduate Students